Physicochemical studies of triazolyl benzoate amphiphile and the effects of different glycolipids towards its critical micellar concentration / Nurul Faiezin Zul - Nurul Faiezin , Zul (2021)
Basic molecular structure of natural fatty acids consisted of polar carboxylic acid headgroup (hydrophilic) connected to non-polar hydrocarbon tail (hydrophobic). However, the addition of a heteroaromatic as a linker between the regions and how they interact within the molecules in self-assembling structure were not well explored. The structure has inspired us to prepare and investigated a synthetic amphiphile constructed from the similar headgroup and alkyl chain but connected by triazolyl group, named as para-decyloxymethyl triazolyl benzoate (p-DMTB). The triazolyl was sufficiently produced from Copper(I)-catalyzed cycloaddition between 4-azidobenzoic acid and alkyl acetylene. Purity and molecular elucidation of the amphiphile were analyzed from 1H and 13C Nuclear Magnetic Resonance (NMR) Spectroscopy, Fourier-Transform Infra-Red (FT-IR) Spectroscopy, Liquid Chromatography-Mass Spectrometry (LC-MS) and elemental analysis. Self-aggregation of p-DMTB in basic condition has been investigated by using various methods such as surface tension, electrical conductivity, absorbance and emission intensity. The results showed that the amphiphile self-aggregated at extremely low concentration (0.10 mM) influenced by the heterocyclic and aromatic moieties in the amphiphile structure. The amphiphile was then investigated in the presence of glycolipids with three different alkyl chain lengths: octyl-β-D-glucopyranoside (OG), decyl-β-D-glucopyranoside (DG) and dodecyl-β-D-glucopyranoside (DDG). Series of mixed p-DMTB-glycolipids solutions have been prepared with a fixed-volume ratio of 9 to 1. The samples were analyzed using surface tension, turbidity and fluorescence spectroscopy measurements. The results suggested that the presence of OG, DG and DDG have disturbed the aggregation of p-DMTB in the mixture solution by increasing the Critical Micellar Concentration (CMC) value of p-DTMB. Consistent with the earlier part of the investigation, p-DMTB without glycolipids was stable due to the headgroup and hydrophobic interactions with additional interaction from aromatic phenyl and heterocyclic triazolyl. However, the presence of glycolipids within p-DMTB aggregation has reduced the effectiveness of interactions that exist within the amphiphile molecules. Therefore, additional interactions such as hydrogen bonding and π-π interaction within p-DMTB molecule could be another co-factor for the amphiphile to self-aggregate more effectively without the presence or help from the glycolipid co-surfactant.